Effect of various fluxes on different metals and alloys in A-TIG process : a review - Chauhan, Rudrang; Sharma, Daulat Kumar; Rana, Bhavesh; Bhayani, Jemish; Borad, Meet (Penerbit Universiti Kebangsaan Malaysia, 2022)
Welding is the process of coalescence of two metals/alloys for creating a seamless joint, is a quintessential fabrication process utilised in almost every manufacturing sector. There is a range of welding processes that are used according to their features and the requirement of the fabricator. The tungsten inert gas (TIG) welding process is an extensively used welding process owing to its inherent characteristics like high weld quality, surface cleanliness, and autogenous welding mode. Unfortunately, the TIG process suffers some drawbacks, the most pronounced one is the shallow weld bead and low depth of penetration (DOP). This renders the process unusable for welding thicker sections in a single pass and consequently requires multiple passes which adds to the expenditure. A modification to this process is the A-TIG welding where A stands for Activated, the method utilises activating flux material to augment the penetration depth and depth to width ratio (DWR) of the weld bead. The current work is comprehensive and focuses mainly on the basics of the A-TIG process, understanding of weld pool dynamics that are governing the depth of penetration, analysis of various flux materials for their effects on different metals/alloys and finally the outcomes fetched from using A-TIG process on different commercially important alloys.